Survival Of The Legacy Airlines - Teoh, Albert Teck Bin (2008)
This project seeks to highlight how tightly interwoven these hidden constraints are on the airlines operation that makes many legacy airline dysfunctional in the face of outdated operating methods that have seize up the company and face extreme difficulties in competing with the new nimble budget airlines that got it right from the start.